2015
DOI: 10.1111/neup.12243
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of phosphorylated α‐synuclein in subpial and periventricular astrocytes in multiple system atrophy of long duration

Abstract: The histological hallmark of multiple system atrophy (MSA) is accumulation of phosphorylated α-synuclein in oligodendrocytes. However, it is uncertain whether phosphorylated α-synuclein accumulates in astrocytes of MSA patients. We immunohistochemically examined the frontal and temporal lobes, basal ganglia, cerebellum, brainstem and spinal cord of patients with MSA (n = 15) and Lewy body disease (n = 20), and also in control subjects (n = 20). Accumulation of abnormally phosphorylated and aggregated α-synucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 52 publications
(62 reference statements)
2
40
1
Order By: Relevance
“…Similar to previous research, 1 the accumulation of α-synuclein in subpial or perivascular astrocytes in the striatum were observed in 11% (16/140) of MSA patients (Table 1). Numerous TSAs were observed around the lenticulostriate arteries (Fig.…”
Section: Letter To the Editorsupporting
confidence: 89%
See 1 more Smart Citation
“…Similar to previous research, 1 the accumulation of α-synuclein in subpial or perivascular astrocytes in the striatum were observed in 11% (16/140) of MSA patients (Table 1). Numerous TSAs were observed around the lenticulostriate arteries (Fig.…”
Section: Letter To the Editorsupporting
confidence: 89%
“…1 The authors revealed that this finding is specific for MSA patients and possibly related with a long disease duration. The morphology and location of this astrocytic pathology are reminiscent of aging-related tau astrogliopathy (ARTAG), which is characterized by thorn-shaped astrocytes (TSA) or granular/fuzzy astrocytes in subependymal, subpial, perivascular, gray matter, and white matter regions.…”
Section: Letter To the Editormentioning
confidence: 94%
“…Nakamura et al reported that these astrocytes were a specific feature of MSA, and that they correlated with disease duration 20. Subsequently, Koga et al found α-synuclein-positive astrocytes in subpial and perivascular regions in both MSA (figure 2P) and Lewy body disease, suggesting this pathology is not a specific feature of MSA 21…”
Section: Neuropathologymentioning
confidence: 99%
“…Both astrogliosis and microgliosis have been observed in MSA brains (Schwarz et al, 1996), and in transgenic mouse models of MSA (Ubhi et al, 2012; Valera et al, 2015; Valera et al, 2014). As-trocytes are able to accumulate α-syn in MSA and in tg mouse models (Mandler et al, 2015; Nakamura et al, 2016), and stimulate the release of pro-inflammatory cytokines (Lee et al, 2010). MSA brains exhibit widespread astrogliosis (Schwarz et al, 1996) correlated to the presence of nearby GCI-positive oligodendrocytes (Radford et al, 2015), suggesting that localized presence of extracellular α-syn may underlie the astrocytic pathology in MSA.…”
Section: The Neuropathology Of Msamentioning
confidence: 99%